Assessment of quality of antenatal care services in Nigeria: evidence from a population-based survey (2015)
Background: The aim of the newly introduced “focused Antenatal Care (ANC)” is not only to achieve a minimum number of 4 visits, but also the timeliness of the commencement of the visits as well as the quality and relevance of services offered during the visits. This study is therefore designed to assess the quality of ANC services in Nigeria. Methods: We used information supplied by the 13410 respondents who claimed to have used the ANC facilities at least once within five year preceding the 2013 Nigeria Demographic and Household Survey (NDHS). Ten components of ANC including: offer of HIV test, Tetanus Toxoid injection, receiving iron supplementation, intermittent preventive treatment (IPT), intestinal preventive drug (IPD), timely ANC enrollment and number of visits were assessed. Receipts of all the ten components were classified as desirable (good) quality of ANC services while receipt of eight critical components among the ten were assumed to be the minimum acceptable quality. Data was weighted and analyzed using descriptive statistics and logistic regression models at 5 % significance level. Results: Measurement of blood pressure and receiving iron supplementation were the most commonly offered ANC component in Nigeria with 91.0 % each while IPD and IPT were given to only 20.7 % and 37.6 % respectively. Less than two thirds were taught on PMTCT while 41.7 % had HIV test and obtained results. Only 4.6 % (95 % CI: 4.2–5.1) of women received good quality of ANC while nearly 1.0 % did not receive any of the components. About 11.3 % (95 % CI: 10.6–11.9 %) of the attendees had minimum acceptable quality of ANC. Receipt of good quality ANC services was higher among users who initiated ANC early, had at least 4 ANC visits, attended to by skilled health workers, attended government and private hospitals and clinics. Higher odds of receiving good quality of ANC were found among users who lives in urban areas, having higher educational attainment, belonging to households in upper wealth quintiles and attended to by skilled ANC provider. Conclusions: The levels of desirable and minimum acceptable quality of ANC services were poor in Nigeria thereby jeopardizing efforts to achieve the MDGs. There is need for intensified commitment by national and state governments in Nigeria as well as other stakeholders to ensure that main components of ANC are received by the users.